Enhancing Business Competitiveness in Running Business Process through using of Internal Capacities of the Textile and Textile Knitting Industry (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article addresses the issues of improving ways to effectively use the domestic potential of the textile and clothing industry. It also covers the development of the textile and clothing industry and the effective use of domestic resources. In addition, indicators have been proposed to identify the internal potential of the textile and clothing industry, and research has been conducted on their evaluation practices. The main indicators of the structure of production capacity and the level of utilization of internal capacity of industrial enterprises have been developed. In addition, the export potential of the industrial sector of the Republic of Uzbekistan was analyzed and the export potential of Samarkand region was assessed. Conclusions and recommendations have been developed to improve the effective use of the domestic potential of the textile and clothing industry.